TECHNOLOGY OF MANUFACTURING CRYSTAL SILICON BASED SOLAR PANELS - Soxibova Zarnigorxon Mutalibjon qizi; Mirzadavlatov Rasuljon Ismoil o‘g‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: this article describes the technologies of making crystalline silicon-based solar panels, improving their chemical, mechanical, and thermal properties, as well as methods of using and connecting solar cells.